Cystic lymphangioma of the mesentery: a case report - Brahmi, Yasser El; Elfahssi, Mohammed; Njoumi, Noureddine; Elhjouji, Abderrahmane; Ait Ali , Abdelmounaim (International Surgery Journal, 2024)
Cystic lymphangioma of the mesentery is a rare benign malformative tumor of the lymphatic vessels. Mesenteric lymphangioma is predominantly encountered during infancy, yet in uncommon instances, it can manifest in adults. Their clinical expression is polymorphic but nonspecific. Diagnosis is suggested by radiology but only histological examination will confirm the diagnosis. Treatment is surgical and the prognosis is good. Complete resection should be performed whenever possible. Intracystic sclerotherapy is possible for unresectable lymphangiomas. The rarity of these tumors, their diagnostic challenges, and the fact that this case involves an adult patient, prompted us to report the following observation.